Characteristics of the formation and development of construction clusters in the conditions of regions - Abdurakhmanov M. A. (Genius Journals, 2022)
The main entities of the regional investment construction cluster include small, medium and large construction enterprises, intermediary services and suppliers of construction services, market infrastructure organizations. Regulation of the activities of the regional investment construction cluster is based on a number of principles. They define the requirements for the structure and management system of the cluster and regulate the activities of the subjects in the cluster
Keywords: Regions; cluster; cluster management; construction complex